2020
DOI: 10.3390/jcm9020449
|View full text |Cite
|
Sign up to set email alerts
|

Consensus-Based Recommendations for Advance Directives of People with Parkinson’s Disease in Regard to Typical Complications by German Movement Disorder Specialists

Abstract: A huge proportion of people with Parkinson’s disease (PwP) in Germany have written an advance directive (AD). However, the content of these forms in regard to specific Parkinson’s disease (PD)-related complications is rather low. There is an urgent need to specify ADs of PwP and consequently to improve decision-making concerning end-of-life aspects for affected patients. Evidence- and consensus-based PD-specific recommendations for ADs might help to close this gap. A Delphi study with two online Delphi rounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…PD-specific recommendations for ADs concerning PD-related complications were evaluated by a group of neurologists and GPs by completing a questionnaire. These consensus-based recommendations were developed in a previous study of our research group [ 5 ]. Physicians were also asked to give their estimation to the current status quo concerning the palliative guidance of their patients with PD.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PD-specific recommendations for ADs concerning PD-related complications were evaluated by a group of neurologists and GPs by completing a questionnaire. These consensus-based recommendations were developed in a previous study of our research group [ 5 ]. Physicians were also asked to give their estimation to the current status quo concerning the palliative guidance of their patients with PD.…”
Section: Methodsmentioning
confidence: 99%
“…As no curative treatment has been found yet, the disease inevitably leads to progressing motor and non-motor symptoms [ 2 ]. Those symptoms can cause a loss of autonomy, forcing the treating physicians to adapt therapies regularly in order to meet the needs of people with PD (PwP) [ 3 , 4 , 5 , 6 , 7 ]. Further, physicians have to support PwP in planning future treatments in advance for when PwP become unable to express their wishes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to diagnostics or treatments that are not within the actual wishes of the patient [ 23 ]. Previous studies reported that a high amount of PD patients have advanced directives, so their use in the inpatient setting should be ensured [ 24 , 25 ]. The emergency box could be of help here, as the advanced directive is mentioned in the inlet as well.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with similar studies [36,40,41], each recommendation was considered consented when ≥ 80% of participants scored the item 1 (strongly agree) or 2 (somewhat agree) for both relevance and feasibility. Although the Delphi method does not require items that achieve a high level of agreement in the first round to be added to the second round [42], in the present study, the authors (F.A.H., L.G.)…”
Section: Data Processing and Analysesmentioning
confidence: 99%